From Interactions to Conversations: The Development of Joint Engagement during Early Childhood - Adamson, Lauren B. (2013)
This research traces the development of symbol-infused joint engagement during mother-child interactions into the preschool years. Forty-nine children, who had been previously observed as toddlers (Adamson, Bakeman, & Deckner, 2004), were systematically observed during interactions with their mothers at ages 3½, 4½, and 5½ during activities related to the past and future, internal states, and graphic systems. Although the amount of symbol-infused joint engagement reached a ceiling by 3½, its focus continued to became more complex and its form more balanced. Individual differences in children’s symbol-infused joint engagement were stable across four years. These findings highlight both how joint engagement is transformed as conversational skills develop and how it remains rooted in earlier interactions and supported by caregiver’s actions.